1967
DOI: 10.1111/j.1467-9450.1967.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

A Serial Afterimage Experiment in Clinical Diagnostics

Abstract: Successive change in the size of negative afterimages repeatedly projected upon a screen was measured in a group of 87 psychiatric patients and a control group of 27. Primitive‐hysteroid subjects were characterized by fluctuating serials, compulsives by small size changes of short duration, anxiety cases by progressively growing, dark, achromatic images, and psychotics by sudden contractions to size‐constant or concrete images. A tentative finding for depressives was also presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1969
1969
1999
1999

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
(1 reference statement)
0
12
1
Order By: Relevance
“…In other words, even the adult A1 cannot merely be regarded as the mechanical result of certain conditions pertaining to the stimulus and projection surface. In individuals suffering from manifest anxiety, for instance, we have shown how AIs become dark, even frightening, and/or cover an in-creasing part of the perceptual field (Smith & Kragh, 1967;Smith, Sjoholm & Nielzen, 1976). It has also been demonstrated that when anxiety is curbed by depressive retardation AIs are likely to gradually diminish and lose their darkness over the experimental serial (Smith, Kragh, Eberhard & Johnson, 1972;Smith & Danielsson, 1978b).…”
Section: G J W Smith Psychological Laboratory Paradisgatan 5mentioning
confidence: 98%
“…In other words, even the adult A1 cannot merely be regarded as the mechanical result of certain conditions pertaining to the stimulus and projection surface. In individuals suffering from manifest anxiety, for instance, we have shown how AIs become dark, even frightening, and/or cover an in-creasing part of the perceptual field (Smith & Kragh, 1967;Smith, Sjoholm & Nielzen, 1976). It has also been demonstrated that when anxiety is curbed by depressive retardation AIs are likely to gradually diminish and lose their darkness over the experimental serial (Smith, Kragh, Eberhard & Johnson, 1972;Smith & Danielsson, 1978b).…”
Section: G J W Smith Psychological Laboratory Paradisgatan 5mentioning
confidence: 98%
“…The apparatus was a slightly modified version of the one used in previous investigations (Smith & Kragh, 1967). Stimulus consisted of a red square with a black fixation point in the middle.…”
Section: Afterimage Experimentsmentioning
confidence: 99%
“…If the above reasoning is correct the degree of adaptation to Emmert's law ought to reflect fundamental aspects of an individual's cognitive maturity. As already shown in a series of investigations (Smith & Kragh, 1967;Smith, Kragh, Eberhard, & Johnson, 1969) variations in afterimage size (together with hue and brightness) over a series of consecutive measurements can be exploited for the description of a variety of central regulatory mechanisms. The present problem, to be sure, concerns only the abandonment of size-constancy and related phenomena.…”
mentioning
confidence: 96%
“…The A1 experiment (Smith & Kragh, 1967) consisted of a semi-transparent screen of ground Plexiglas which moved along a horizontal bar. Attached to the front of the screen were two vertical rulers manipulated by S for the measurement of A1 size.…”
Section: Afterimage Experinrentmentioning
confidence: 99%
“…The two aftereffects to be compared here have both been utilized separately as indicators of various personality dimensions in clinical settings (Andersson, 1967b;Smith & Kragh, 1967;Smith, Kragh, Eberhard, & Johnson, 1969). .…”
mentioning
confidence: 99%